UPAYA HUKUM DALAM PENYELESAIAN WANPRESTASI PERJANJIAN PINJAM MEMINJAM UANG PADA KOPERASI UNIT DESA DALAM MENDUKUNG PEMBANGUNAN EKONOMI DAERAH - Surya, Kadek Adi; I Dewa Nyoman Gde Nurcana; I Wayan Suradigama; I Made Suandana (Universitas Tabanan, 2025)
This study aims to analyze the legal regulations concerning the resolution of breach of contract in loan agreements within Village Unit Cooperatives (KUD) and its relevance to supporting regional economic development. Breach of contract issues in cooperative credit activities can disrupt the financial stability of the institution and hinder its strategic role in the local economy. This research uses a normative legal method with a statutory and doctrinal approach, referring to both primary and secondary legal sources. The results indicate that the legal framework for resolving breach of contract in KUD is based on Article 33 of the 1945 Constitution, Law Number 25 of 1992 concerning Cooperatives, and the provisions in Law Number 30 of 1999 concerning Arbitration. The application of dispute resolution mechanisms through mediation and arbitration provides effective alternatives to court proceedings. The relevance of this legal regulation is crucial, as KUD plays a role in agricultural product distribution, microcredit provision, and the empowerment of a people-based economy grounded in mutual cooperation. With legal certainty in handling breaches of contract, the operational sustainability of KUD can be maintained, thereby contributing to sustainable regional economic development.